BUMG Yang Mensejahterakan, Antara Peluang Dan Tantangan (Studi Dilingkungan Pemerintah Kota Lhoksuemawe) - Muhammad Muhammad; Rudi Kurniawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The policy of issuing Law Number 6 of 2014 concerning Villages is the basis for allocating funds for development and empowerment of villages, which are the basis of society and the nation at the lowest level of government called Gampong. The funds allocated for the Gampong come from the APBN, Provincial APBD or Regency / City APBK. Through this policy, it is hoped that the Gampong will develop into an independent Gampong that is able to organize and take care of itself. The allocation of Gampong funds is directed to finance government activities, development and community empowerment. Specifically for the economic sector in Gampong, the government established a Village-Owned Enterprise (BUMG) which is a strategic business driver for collective economic development in order to improve the quality of life and create a prosperous society. BUMG is a form of Gampong economic independence with financial support through APBK as a capital to move strategic and potential business units based on local wisdom, with the final hope that there will be a transformation from a helpless village to a more capable and government driven village to a capable independent village organize and take care of itself. BUMG must be able to compete in today's global era with the right strategy, and BUMG must act as a social entrepreneur who not only prioritizes profit but pays more attention to the welfare of the community. To determine the potential business berkearifan riel local businesses, conducted through a SWOT analysis with a focus on internal factors BUMG ie Strength (Strength) and weakness (Weakness) owned and external factors that are Opportunities (Opportunities) and Challenge (Threats).With a SWOT analysis, it finally makes it easier to apply the concept of a plan as a step to develop a future BUMG model.